PENGARUH LOCUS OF CONTROL, GOAL ORIENTATION DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PT. SINAR ABADI SPARK PLUS PALU - Franki, Franki (Katalogis, 2015)
This research intends to determine and analyze : 1) simultaneous effects of locus of control, goal orientation and organizational culture on employees’ performance at PT. Sinar Abadi Spark Plus Palu, 2) the influence of locus of control on employees’ performance at PT. Sinar Abadi Spark Plus Palu, 3) the influence of goal orientation on employees’ performance at PT. Sinar Abadi Spark Plus Palu, and 4) the influence of organizational culture on employees’ performance at PT. Sinar Abadi Spark Plus Palu. This research is descriptive and it means to show the influenceof locus of control, goal orientation and organizational culture on employees’ performance by interviewing 65 respondents that are selected through purposive sampling method. Based on the results of multiple linear regressions analysis, it can be concluded: 1) locus of control, goal orientation and organizational culture simultaneously have positive and significant effects employees’ performance at PT. Sinar Abadi Spark Plus Palu, 2) locus of control partially has positive and significant effects employees’ performance at PT. Sinar Abadi Spark Plus Palu, 3) goal orientation partially has positive and significant effects employees’ performance at PT. Sinar Abadi Spark Plus Palu, 4) organizational culture partially has positive and significant effects employees’ performance at PT. Sinar Abadi Spark Plus Palu.